2020
DOI: 10.1007/s40430-020-02396-1
|View full text |Cite
|
Sign up to set email alerts
|

Robust project of resonant shunt circuit for passive vibration control of composite structures

Abstract: Composite structures have been widely used in petroleum, aerospace and automotive industries for which structural components must be designed to support high levels of mechanical disturbances with typically high reliability levels. Moreover, the increasing high-speed and lightweight composite structures subjected to vibrations, and the interest in achieving vibration attenuation becomes capital importance as extensive vibrations can reduce structural life and contribute to mechanical failure. In this sense, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Variabilities in the media break its periodicity, causing disorder that affects the wave propagation and dynamic performances [34,35]. The problem of vibration control using resonant shunts with random electrical components was analysed in [36,37]. Porfiri and Andreaus [38] showed that the circuit's resonance may be lost when the electrical impedance varies concerning its optimal value, which is a crucial issue in quantifying the effect of electrical parameters variations on the system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Variabilities in the media break its periodicity, causing disorder that affects the wave propagation and dynamic performances [34,35]. The problem of vibration control using resonant shunts with random electrical components was analysed in [36,37]. Porfiri and Andreaus [38] showed that the circuit's resonance may be lost when the electrical impedance varies concerning its optimal value, which is a crucial issue in quantifying the effect of electrical parameters variations on the system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pode-se citar como exemplo as vibrações causadas pela ressonância solo em helicópteros (SANCHES; RADE, 2013), como ilustrado na Neste sentido, a atenuação de vibrações e ruído de sistemas é parte importante de qualquer projeto de engenharia, de modo que a predição do seu comportamento requer que tanto o procedimento de modelagem como o de sua caracterização seja confiável. Dentre as várias técnicas de controle de vibrações existentes (RIBEIRO et al, 2020;GONÇALVES et al, 2019;CUNHA-FILHO et al, 2016), as técnicas de controle passivo via emprego de materiais viscoelásticos apresentam muitas vantagens, a saber: não conferem instabilidade ao sistema; são eficientes numa ampla faixa de frequência; baixo custo de instalação e manutenção; e seu funcionamento não requer consumo externo de energia. A principal desvantagem é que sua eficiência depende tanto da frequência de excitação como da temperatura de operação do material viscoelástico.…”
Section: Contexto Do Estudounclassified